KNOWLEDGE EXTRACTION ON REDUCING THE NUMBER OF STUDENTS USING EXPLORE, ELABORATE AND EXECUTE TECHNIQUES - Guterres, Juvinal Ximenes; Iriani, Ade; Purnomo, Hindriyanto Dwi (Universitas Muhammadiyah Surakarta, 2019)
The decline in the number of students at East Timor's private universities can create new problems. This will be a burden for universities and other private institutes to develop. The financial and financing components are the factors that determine the implementation of teaching and learning activities that are used, among others, for the cost of facilities and teaching equipment. This study aims to extract knowledge of the decline in the number of students that occur every year at UNITAL. The method used is knowledge capture with Explore, Elaborate, and Execute techniques. Data collection techniques carried out by observation, interviews, documentation and questionnaires. Explore techniques to investigate results data, observations, interviews, documentation and questionnaires related to the reduction in the number of students arrested in the form of causes and effects of problems, then elaborate techniques describe interview, observation, brainstorming, and documentation data. The execute process is the stage of executing data from knowledge capture techniques based on explore and elaborate techniques and then produces a tacit and explicit knowledge from the actors or actors. The results obtained from this research are able to identify that the decline in students is caused by the main factors, namely, the quality of human resources consisting of lecturers, staff and technicians, service quality, facilities and infrastructure, buildings, classrooms, laboratory facilities, libraries and UNITAL academic information systems. Externally, there is a lack of cooperation with universities, both domestic and foreign, promotion to the public both directly and through social media. The results of knowledge capture is wealth that can be stored in a repository to be shared to help the processing of knowledge with the help of Information Technology.